2011
DOI: 10.1093/bja/aer323
|View full text |Cite
|
Sign up to set email alerts
|

Nitrous oxide (N2O) reduces postoperative opioid-induced hyperalgesia after remifentanil–propofol anaesthesia in humans

Abstract: Intraoperative 70% N(2)O administration significantly reduced postoperative OIH in patients receiving propofol-remifentanil anaesthesia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(56 citation statements)
references
References 33 publications
0
55
0
1
Order By: Relevance
“…48 Nevertheless, there is a lack of clinical trials evaluating the role of N 2 O to reduce PPSP. One retrospective analysis of data from a study designed for other purposes suggested a likely preventive effect of N 2 O to decrease PPSP.…”
Section: Ketaminementioning
confidence: 99%
See 1 more Smart Citation
“…48 Nevertheless, there is a lack of clinical trials evaluating the role of N 2 O to reduce PPSP. One retrospective analysis of data from a study designed for other purposes suggested a likely preventive effect of N 2 O to decrease PPSP.…”
Section: Ketaminementioning
confidence: 99%
“…48 Néanmoins, il n'y a pas d'étude clinique qui a évalué le rôle du N 2 O dans la réduction des DCPC. Seule une analyse rétrospective de données émanant d'une étude conçue à d'autres fins a suggéré un effet préventif probable de l'administration de N 2 O peropératoire sur les DCPC.…”
Section: Kétamineunclassified
“…In another rat study, the NMDA receptor antagonist activity shown by N 2 O was seen to prevent hyperalgesia induced by opioids [8]. Therefore in a clinical study by Echeverria et al, they were shown that intraoperative 70% N 2 O administration significantly reduced postoperative opioid induced hyperalgesia in patients after septorhinoplasty operation [15]. A subgroup follow-up analysis of Enigma trial showed that intraoperative nitrous oxide administration was associated with a reduced risk of chronic postsurgical pain [16].…”
Section: Discussionmentioning
confidence: 97%
“…Several studies have shown some usefulness on the prevention of a potential hyperalgesia related to perfusion of some opioids [2], and the decreased occurrence of postoperative chronic pain [23]. Moreover, the use of N 2 O has been established has a good practice [24], namely for promoting faster recoveries in the ambulatory surgery scenario [24].…”
Section: Nitrous Oxidementioning
confidence: 99%
“…This idea is growing in several areas, namely about the indication and safety to anesthetize pediatric patients [1], the use of intravenous infusions of opioids that might be related to the development of hyperalgesia [2], the advantages and drawbacks of the amount of oxygen to use [3] or even the current indication for the use of nitrous oxide [4].…”
Section: Introductionmentioning
confidence: 99%